Fine mapping and expression characteristics analysis of male-sterile gene BrRNR1 in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Meihui Xue; Jiahang Li; Ruiqi Liao; Junjie Xu; Mingwei Zhou; Runpeng Yao; Zhiyong Liu; Hui Feng; Shengnan Huang (BMC Plant Biology)
Abstract Background Chinese cabbage is a cross-pollinated crop with remarkable heterosis, and male-sterile line is an important mean to produce its hybrids. In this study, a male-sterile mutant msm7 was isolated from a Chinese cabbage DH line ‘FT’ by using EMS-mutagenesis. Results Compared with the wild-type ‘FT’, the anthers of mutant msm7 were completely aborted, accompanied by the defects in leaf and petal development. Genetic analysis showed that a single recessive nuclear gene controlled the sterile phenotype of mutant msm7. Cytological observation indicated that the anther abortion of mutant msm7 was caused by the degenarated microspores and premature degradation of tapetum. MutMap and KASP analyses identified that BraA01g038270.3 C, encoding the large subunit of ribonucleotide reductase (RNR1) which involved in the biosynthesis of dNTPs, was the candidate gene, named BrRNR1. Compared with the wild-type ‘FT’, a G-A mutation occurred on the 4th exon of the BrRNR1 gene, leading to the premature termination of encoded amino acid in mutant msm7. Expression analysis indicated that the BrRNR1 gene was ubiquitously expressed in all organs and was significantly decreased in flower bud and anther of mutant msm7 compared with the wild-type ‘FT’. Subcellular localization revealed that BrRNR1 was an endoplasmic reticulum localization protein. Conclusion Our study is the first to characterize the function of BrRNR1 gene associated with male sterility and lays a foundation for exploring the molecular mechanism of anther abortion caused by the mutation in BrRNR1 gene of Chinese cabbage.